Vibe Marketing and AI-Generated Content: Examining Consumer Trust, Perceived Authenticity, and Purchase Intention in the Age of Artificial Intelligence - Zainurrafiqi Zainurrafiqi; Istianah Asas; Enza Resdiana; Isnain Bustaram; Adriani Kusuma; Nurul Hidayati; Aang Kunaifi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the impact of vibe marketing and AI-generated content on consumer trust, perceived authenticity, and purchase intention. The sample consists of 200 consumers aged 18-45 who actively use digital platforms. The research uses a quantitative method with analysis through WarpPLS. The results show that vibe marketing has a positive effect on consumer trust, which in turn increases purchase intention. Additionally, AI-generated content influences perceived authenticity, which also affects consumers' purchase intention. The study also finds that consumer trust acts as a mediator in the relationship between vibe marketing and purchase intention. These findings provide important insights for developing more effective and ethical AI-based marketing strategies.